Ether / ester composite polyurethane foam for cosmetics

The ester/ether composite polyurethane foam with a specific ether/ester ratio addresses the imbalance in hydrolysis and oil resistance, enhancing the discharge and comfort of cushion cosmetics by ensuring stable and uniform cosmetic distribution.

JP7604737B2Active Publication Date: 2024-12-24COSMAX INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2020566285
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-10-30
Filing Date
2018-11-21
Publication Date
2024-12-24
Estimated Expiration
2038-11-21

AI Technical Summary

Technical Problem

Conventional polyurethane foams used in cosmetics lack a balanced combination of hydrolysis resistance, oil resistance, and cell structure adjustment, leading to inadequate performance in cushion cosmetics.

Method used

A cosmetic product comprising an ester/ether composite polyurethane foam with a specific ether/ester ratio of 4:6 to 6:4, which includes a cosmetic composition with controlled water content, shear stress, and emulsifier ratios to achieve stable and uniform discharge.

Benefits of technology

The composite polyurethane foam provides improved chemical resistance, flow properties, and reduced hardness change upon impregnation, resulting in a more comfortable and effective cosmetic application experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604737000012
    Figure 0007604737000012
  • Figure 0007604737000013
    Figure 0007604737000013
  • Figure 0007604737000014
    Figure 0007604737000014
Patent Text Reader

Abstract

The present invention relates to a cosmetic comprising a polyurethane foam impregnated with a liquid cosmetic composition. The present invention provides a cosmetic comprising a polyurethane foam impregnated with a cosmetic composition, wherein the polyurethane of the polyurethane foam contains ether groups and ester groups in a molar ratio of 4:6 to 6:4, and the cosmetic composition has a water content of 35 wt% or less and a critical shear stress value where the storage modulus (G') = loss modulus (G'') is 100 Pa or less. The present invention can provide a cosmetic comprising a composite polyurethane foam in which the cosmetic composition is stably supported and can be uniformly redistributed within the foam when pressurized.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a cosmetic product, and more particularly to a cosmetic product comprising a polyurethane foam impregnated with a liquid cosmetic material. [Background technology]

[0002] Cosmetics are available in various forms, such as solid and liquid, and liquid cosmetics are generally placed in flexible containers, such as tubes, to prevent leakage and facilitate easy discharge.

[0003] Recently, cushion cosmetics have been used in which a liquid cosmetic having low or high viscosity is impregnated into an impregnating material such as polyurethane foam, and then the polyurethane foam is pressurized using a tool such as a puff so that the cosmetic is discharged by adhering to the puff.

[0004] Conventionally, polyurethane foam has been mainly used as an impregnating material for such cosmetics, and such polyurethane foam is classified into ether-based polyurethane foam and ester-based polyurethane foam according to the type of polyol used in the polymer polymerization reaction. Ether-based polyurethane foam has the advantages of excellent hydrolysis resistance, excellent elasticity, and low cost, but has the disadvantage of poor oil resistance, while ester-based polyurethane foam has the advantages of easy bubble adjustment, excellent abrasion resistance, chemical resistance, etc., but has the disadvantage of being easily hydrolyzed. Therefore, the use of polyurethane foam that compensates for the disadvantages of the two polyols and highlights their advantages is required.

[0005] Furthermore, in conventional cushion cosmetics, there is absolutely no consideration given to the foam material or foam structure, no consideration given to the required properties of a cosmetic composition suitable for such a foam, and no design of a cosmetic composition based on such properties. Summary of the Invention [Problem to be solved by the invention]

[0006] In order to solve the problems of the prior art, the present invention aims to provide a cosmetic product comprising an ester / ether composite polyurethane foam having a specific ether / ester ratio.

[0007] Another object of the present invention is to provide a polyurethane foam cosmetic comprising a cosmetic composition having flow properties suitable for use under pressure.

[0008] More specifically, an object of the present invention is to provide an ether / ester polyurethane foam cosmetic product having chemical resistance and flow properties suitable for pressurized use. [Means for solving the problem]

[0009] In order to achieve the above technical objectives, the present invention provides a cosmetic comprising a polyurethane foam impregnated with a cosmetic composition, wherein the polyurethane of the polyurethane foam contains ether groups and ester groups in a molar ratio of 4:6 to 6:4, and the cosmetic composition has a water content of 35 wt% or less and a critical shear stress value, where storage modulus (G') = loss modulus (G''), of 100 Pa or less.

[0010] In the present invention, the water content of the cosmetic composition may be 20 to 35 wt %, or 20 to 30 wt %, or 25 to 30 wt %.

[0011] In the present invention, the critical shear stress value of the cosmetic composition may be 20 Pa or less, 10 Pa or less, or 5 Pa or less.

[0012] In the present invention, the cosmetic composition preferably satisfies the relationship 3≦G′ / G″≦10 under a shear stress of 1 Pa.

[0013] In the present invention, the cosmetic composition contains an oil phase component and an aqueous phase component, and the weight ratio of the oil phase component to the aqueous phase component is preferably in the range of 0.9 to 1.1.

[0014] The cosmetic composition preferably contains a primary emulsifier and an auxiliary emulsifier, and the primary emulsifier and the auxiliary emulsifier are preferably in a weight ratio of 3:1 to 4:1.

[0015] In this case, it is preferable that the primary emulsifier includes at least one substance selected from the group consisting of lauryl PEG-10 tris(trimethylsiloxy)silylethyl dimethicone, lauryl PEG-9 polydimethylsiloxyethyl dimethicone, and cetyl PEG / PPG-10 / 1 dimethicone, and the auxiliary emulsifier includes at least one of PEG-10 dimethicone and sorbitan isostearate.

[0016] In the present invention, the hardness of the polyurethane foam after impregnation is preferably 20 to 35. At this time, it is more preferable that the hardness change rate before and after the impregnation based on the hardness before the impregnation is 45% or less. Effect of the Invention

[0017] According to the present invention, it is possible to provide a cosmetic product comprising an ester / ether composite polyurethane foam having a specific ether / ester ratio.

[0018] Furthermore, according to the present invention, a cosmetic product can be provided that includes a composite polyurethane foam in which a cosmetic composition is present in a stable state when supported and which can be uniformly rearranged inside the foam when pressurized. [Brief description of the drawings]

[0019] [Figure 1] 1 is a schematic diagram illustrating a cosmetic product according to an embodiment of the present invention. [Diagram 2] FIG. 1 is a diagram conceptually showing the structure of the impregnating material of the present invention in two dimensions. [Diagram 3]FIG. 2 is a schematic diagram for explaining the behavior of an impregnating material and a cosmetic composition in the present invention. [Figure 4] FIG. 2 is a schematic diagram for explaining the flow of a cosmetic composition according to an embodiment of the present invention. [Diagram 5] 1 is a graph showing the flow characteristics of a cosmetic composition according to an embodiment of the present invention. [Figure 6] 4 is a graph showing the flow characteristics of a cosmetic composition according to another embodiment of the present invention. [Figure 7] 4 is a graph showing flow characteristics of a cosmetic composition according to still another embodiment of the present invention. [Figure 8] 1 is a graph showing the results of measuring hardness of a polyurethane foam before and after impregnation according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The present invention will now be described in detail by describing preferred embodiments of the present invention with reference to the drawings.

[0021] In the present specification, the term "ether polyurethane foam" refers to a foamed polyurethane formed by reacting a polyether polyol with a compound having an isocyanate (-NCO) group. The term "ester polyurethane foam" refers to a foamed polyurethane formed by reacting a polyester polyol with a compound having an isocyanate (-NCO) group. The term "ether / ester polyurethane foam" refers to a foamed polyurethane formed by reacting a mixture of a polyether polyol and a polyester polyol with a compound having an isocyanate (-NCO) group, or a foamed polyurethane formed by reacting a hybrid copolymer of a polyether polyol and a polyester polyol with a compound having an isocyanate (-NCO) group. The term "ether:ester ratio" refers to the molar ratio of ester groups and ether groups in an ether / ester polyurethane foam. For example, "ether:ester=4:6" means that the molar ratio of ether groups and ester groups in the polyurethane is 4:6.

[0022] FIG. 1 is a schematic diagram of a cosmetic product according to an embodiment of the present invention.

[0023] As shown in the figure, the cosmetic product 10 includes a container body 11 for containing a liquid cosmetic material. The container body 11 contains the liquid cosmetic material in an impregnating material 100. The cosmetic product may include an inner lid 13 and / or an outer lid 15 for preventing leakage of the liquid cosmetic material from the form 100. Although not shown, a fastener for fixing the three-dimensional woven fabric impregnating material may be further provided to prevent the three-dimensional woven fabric impregnating material from coming off. This will be described later.

[0024] In the present invention, the impregnating material 100 is preferably an ether-ester polyurethane foam. More preferably, the ether-ester polyurethane foam is an intermediate ratio ether-ester polyurethane foam. Here, the intermediate ratio means that the ratio of ester groups in the polyurethane is close to half, and for example, the ratio of ether:ester is preferably 4:6 to 6:4.

[0025] For example, the ether:ester ratio may be 4:6 to 6:4, preferably 4.5:5.5 to 5.5:4.5, and more preferably 4.3:5.7 to 5.7:4.3. In some embodiments of the present invention, a polyurethane foam having an ether:ester ratio of 5:5 is used. Although some documents disclose a mixture of polyether polyol and polyester polyol in polyurethane foam, there have been no documents published that have studied the properties or confirmed the effects of polyurethane foam in which polyester polyol, which has been known to be weak in hydrolysis resistance, is used in the raw material at a ratio similar to that of polyether polyol, as in the present invention.

[0026] In the present invention, the behavior of the cosmetic composition discharged from the impregnated material impregnated with the liquid cosmetic composition can be explained as follows.

[0027] The impregnating material is a porous foam, and is composed of cells or lattices as units. A cell can be defined as a skeleton and pores inside the skeleton. In the present invention, the skeleton of the cell has at least a part or all of the cell walls constituting the unit lattice that are in a penetrating state, and the pores of the skeleton are in a mutually connected state, which is called an open pore structure or a network structure.

[0028] 2 is a two-dimensional conceptual diagram of the structure of the impregnating material 20 of the present invention. The cells are composed of a skeleton 12 and internal pores 14 defined by the skeleton. In the drawing, the skeleton 12 is shown as dividing each cell, but when viewed three-dimensionally, the skeleton 12 of the cells has open walls, and adjacent cells communicate with each other.

[0029] The discharge characteristics of the foam cosmetic of the present invention based on the cell structure of Fig. 2 will be conceptually explained with reference to Fig. 3. However, the following explanation is supplementary for understanding the present invention and is not intended to limit the technical idea of ​​the present invention.

[0030] As shown in Fig. 3(a), the impregnating material 10 is impregnated with a liquid cosmetic composition 20. When pressure is applied to the surface of the impregnating material 10 with a puff or a finger, stress is applied to the impregnating material 10 and the cosmetic composition 20. As shown in Fig. 3(b), the unit cells in the impregnating material are deformed by the pressure, and the liquid cosmetic flows inside the cells and between adjacent cells. At this time, the skeleton of the cells acts as a resistance to the flow of the liquid cosmetic, and as a result, part or all of the pressure force acting vertically downward acts as a shear stress on the liquid cosmetic in the impregnating material. The shear stress acting on the cosmetic in this way affects the flow characteristics of the cosmetic composition, which will be described later.

[0031] In polyurethane foams constituting the impregnating material, foams using polyether polyol as a raw material have the advantages of being very excellent in hydrolysis resistance, excellent in elasticity, and inexpensive, but have the disadvantage of being weak in oil resistance. On the other hand, foams using polyester polyol have the advantages of being easy to adjust the bubbles and excellent in abrasion resistance and chemical resistance, but are known to have the disadvantage of being prone to hydrolysis and breaking down when stored at high temperatures for a long period of time. In the present invention, the ether-ester polyurethane foam can make up for the disadvantages of monocomponent polyether foam or polyester foam. Furthermore, polyester polyurethane foam has the advantage of being easier to adjust the cell size compared to polyether polyurethane, and is advantageous for producing polyurethane foams with smaller cell sizes.

[0032] The content (molar ratio) of ester groups in the polyurethane of the foam of the present invention is close to the content (molar ratio) of ether groups, and the molar ratio of ether:ester may preferably be in the range of 6:4 to 4:6. For example, in the present invention, the molar ratio of ether:ester is determined by the mixing ratio of polyether polyol and polyester polyol. That is, a polyurethane with ether:ester=5:5 is produced by mixing polyether polyol and polyester polyol in a ratio of 5:5.

[0033] In the present invention, the cell size in the polyurethane foam can be expressed by the number of pores. In the present invention, the number of pores may be about 70ppi to about 250ppi, about 80ppi to about 250ppi, about 90ppi to about 250ppi, about 100ppi to about 250ppi, about 110ppi to about 250ppi, about 120ppi to about 250ppi, or about 150ppi to about 250ppi, but is not limited thereto. Preferably, the number of pores may be 110ppi or less, 150ppi or less, or 200ppi or less.

[0034] The pore number is defined as the number of pores present in a 1-inch long sample of the foam. Specifically, the pore number is measured according to a standard such as JIS K6400-1, and is as follows:

[0035] Take a specimen with a thickness of 10 mm and width and length of 100 mm, place the specimen on a stand under a magnifying glass with a scale of 5 to 10 times magnification, and count the number of cells within a straight line of 10 mm while moving the magnifying glass or the specimen. At this time, there are three measurement positions, and the average value of the three measurement positions is the number of cells, which can be calculated using the following mathematical formula 1.

[0036] (mathematical formula 1) N = n x 2.54 (where N is the number of cells (pcs / 25.4 mm), and n is the number of cells in a 10 mm interval (average))

[0037] The cell size can also be expressed by the size of the pore. In the present invention, the size of the pore may be about 0.1 mm to about 0.6 mm, about 0.15 mm to about 0.6 mm, about 0.20 mm to about 0.6 mm, about 0.25 mm to about 0.60 mm, or about 0.30 mm to about 0.60 mm, but is not limited thereto. Preferably, in the present invention, the size of the pore is 0.5 mm or less. For example, the size of the pore may be 0.1 mm to 0.5 mm, 0.2 mm to 0.5 mm, or 0.3 mm to 0.5 mm.

[0038] In addition, the present invention can use a foam in which the degree of deformation of the foam caused by pressure is appropriately controlled. For example, the elastic modulus or hardness of the polyurethane foam can be appropriately controlled in the present invention. For example, the hardness of the foam can be adjusted by controlling the molecular weight of the polyol participating in the urethane reaction.

[0039] In accordance with another aspect of the present invention, the polyurethane foam can have a low hardness value and provide good durability.

[0040] In the present invention, the hardness of the polyurethane foam may be in the range of about 30 to about 60, about 35 to about 60, or about 40 to about 60, based on an ASKER hardness scale Type F before impregnation with the cosmetic composition. In addition, the hardness of the polyurethane foam of the present invention may be 55 or less, 50 or less, or 45 or less, but is not limited thereto.

[0041] In the present invention, the hardness of the polyurethane foam after impregnation with the cosmetic composition may be in the range of about 20 to about 40, about 25 to 40, or about 30 to 40. In addition, the hardness of the polyurethane foam of the present invention may be in the range of 20 to 35.

[0042] The hardness value of the polyurethane foam of the present invention is considerably lower than that of general polyurethane foams, which have an ASKER hardness of about 70 to 90 (before impregnation) and about 40 to 45 after impregnation, based on Type F. However, the polyurethane foam of the present invention has the characteristics of having a lower hardness and not decreasing in durability compared to other polyurethane foams currently on the market, and also has excellent hydrolysis resistance and oil resistance as described above.

[0043] On the other hand, when a cosmetic composition is impregnated into an impregnating material, the hardness of the material after impregnation generally decreases, but since the hardness does not decrease to the same value in all impregnating materials, if the difference in hardness before and after impregnation is excessively large, it is difficult to design the cosmetic composition to be impregnated into the impregnating material, and this has a negative impact on the comfort of the cosmetic product after impregnation. The present inventors have continued their research into polyurethane foam that minimizes the difference in hardness before and after impregnation with a cosmetic composition and has excellent comfort and effects, and have completed the present invention.

[0044] In the present invention, the reduction rate of hardness of the polyurethane foam after impregnation with the cosmetic material relative to the hardness before impregnation ((hardness before impregnation-hardness after impregnation) / hardness before impregnation) may be less than 50%, and preferably less than 45%. If the reduction rate is 50% or more, the swelling of the impregnating material after impregnation may become excessively large, affecting the physical properties of the impregnating material and making it uncomfortable to use.

[0045] Furthermore, it was experimentally confirmed that the polyurethane foam of the present invention received a much higher evaluation in terms of "feel in use", which is one of the important sensory characteristics when using cosmetics containing polyurethane foam as an impregnating material, than cosmetics containing different polyol ratios in the past, as can be confirmed from the experimental examples described below. This is because it was determined that polyurethane foam with a hardness of about 20 to about 35 after impregnation with a cosmetic composition is the softest when the impregnated cosmetic composition is applied using an applicator, and the amount of cosmetic composition applied to the applicator is appropriate.

[0046] In the present invention, the polyurethane foam is produced by reacting a mixture of a polyether polyol and a polyester polyol with a compound having an isocyanate (--NCO) group.

[0047] The monomer of the polyether polyol may include, but is not limited to, an alkylene oxide selected from the group consisting of an alkylene oxide, a diol, a triol, or a combination thereof, and the monomer of the polyester polyol may include, but is not limited to, an organic acid having two or more carboxyl groups. In one embodiment of the present application, the monomer of the polyether polyol may include, but is not limited to, an alkylene oxide selected from the group consisting of ethylene oxide and propylene oxide; a diol selected from the group consisting of dipropylene glycol (hereinafter referred to as "DPG"), mono-ethylene glycol (hereinafter referred to as "MEG"), and propylene glycol (hereinafter referred to as "PG"); or a triol selected from the group consisting of glycerin and trimethylol propane (hereinafter referred to as "TMP"); or a combination thereof. In one embodiment of the present application, the polyether polyol includes, but is not limited to, one obtained by addition polymerization of an alkylene oxide such as propylene oxide or ethylene oxide to an initiator having an activated hydrogen.The initiator mainly includes those having two functional groups, such as propylene glycol, dipropylene glycol, ethylene glycol, diethylene glycol, diethanol amine, bisphenol, water, etc., and those having three functional groups, such as glycerine, trimethylol propane, triethanol amine, haxanetriol, etc., but is not limited thereto.

[0048] In the present invention, the monomer of the polyester polyol includes a polyvalent organic acid having two or more carboxyl groups and a carbon number of about 2 to about 20, for example, a higher fatty acid, a saturated fatty acid, or an unsaturated fatty acid, but is not limited thereto. For example, the carbon number of the polyvalent organic acid may be about 2 to about 20, about 2 to about 18, about 2 to about 16, about 2 to about 14, about 2 to about 12, about 2 to about 10, about 2 to about 8, about 2 to about 6, or about 2 to about 4. In one embodiment of the present application, the polyvalent organic acid having two or more carboxyl groups may include, for example, a selected one from the group consisting of adipic acid, oxalic acid, and succinic acid, but is not limited thereto. In one embodiment of the present application, the monomer of the polyester polyol may include, for example, a selected one from the group consisting of soybean oil, castor oil, citric acid, palmitic acid, myristic acid, oleic acid, stearic acid, linoleic acid, and linolenic acid, but is not limited thereto.

[0049] In the present invention, the compound having an isocyanate (-NCO) group includes, but is not limited to, those selected from the group consisting of aromatic, alicyclic, aliphatic, and other polyisocyanates having two or more isocyanate groups, combinations of two or more of the polyisocyanates, and modified polyisocyanates obtained by modifying these. In one embodiment of the present application, the compound having an isocyanate (-NCO) group includes methylene diphenyl diisocyanate (hereinafter referred to as "MDI"), toluene diisocyanate (hereinafter referred to as "MDI"), and the like. Aromatic diisocyanates such as 2,4- or 2,6-tolylene diisocyanate, xylylene diisocyanate (XDI), paraphenylene diisocyanate, 1,5-naphthalene diisocyanate, and tolidine diisocyanate; aliphatic diisocyanates having an aromatic ring such as α,α,α',α'-tetramethylxylylene diisocyanate; methylene diisocyanate, propylene diisocyanate, lysine diisocyanate, 2,2,4- or 2,4,4-trimethylhexyl diisocyanate; The diisocyanate may be an aliphatic diisocyanate such as hexamethylene diisocyanate, 1,6-hexamethylene diisocyanate (HMDI), or an alicyclic diisocyanate such as 1,4-cyclohexane diisocyanate, methylcyclohexane diisocyanate (hydrogenated TDI), 1-isocyanato-3-isocyanatomethyl-3,5,5-trimethylcyclohexane (IPDI), 4,4'-dicyclohexylmethane diisocyanate, isopropylidenedicyclohexyl-4,4'-diisocyanate, or a combination thereof, but is not limited thereto.

[0050] The characteristics of the cosmetic composition suitable for impregnating the ether-ester polyurethane foam of the present invention described above will be described below.

[0051] In order to compensate for the hydrolysis characteristics of the polyurethane foam having a high ester content, the cosmetic composition of the present invention has a low water content. Preferably, the water content of the cosmetic composition is 35 wt% or less, more preferably 30 wt% or less. Exemplarily, the water content of the cosmetic composition may be about 20 to 35 wt%, 20 to 30 wt%, or 25 to 30 wt% in the cosmetic composition.

[0052] In addition, in the present invention, the cosmetic composition has the following flow characteristics.

[0053] The flow characteristics of the cosmetic of the present invention can be expressed by the storage modulus (G') and loss modulus (G''), which indicate the elasticity and viscosity of the composition.

[0054] FIG. 4 is a schematic diagram illustrating the flow of a cosmetic composition according to an embodiment of the present invention. Referring to FIG. 4, when no shear stress is applied, the storage modulus of the composition is greater than the loss modulus (G''). The storage modulus is an index showing the elastic properties of a material, and when no shear stress is applied, the composition behaves like a solid, i.e., behaves like a solid. However, when a shear stress is applied and the stress increases, the storage modulus gradually decreases, resulting in a reversal of the storage modulus and loss modulus values. At this time, Storage modulus ( G' ) curve and loss modulus ( G'' ) at the intersection with the curve The shear stress is defined as the threshold shear stress (σ t ), and if the shear stress exceeds a threshold value, the composition is in a state where the viscous properties dominate, i.e., G''>G', i.e., it exhibits liquid-like behavior. At this time, the composition behaving like a liquid has flow properties close to those of a liquid and can easily flow between the cells of the impregnating material.

[0055] The cosmetic composition of the present invention has a low threshold shear stress. t ) may be about 100 Pa or less, about 90 Pa or less, about 80 Pa or less, about 70 Pa or less, about 60 Pa or less, about 50 Pa or less, about 40 Pa or less, about 30 Pa or less, about 20 Pa or less, about 10 Pa or less, about 9 Pa or less, about 8 Pa or less, about 7 Pa or less, about 6 Pa or less, about 5 Pa or less, 4 Pa ​​or less, 3 Pa or less, 2 Pa or less, or 1 Pa or less. Preferably, the critical shear stress of the composition is in the range of 1 Pa to 20 Pa, 2 to 20 Pa, or 3 to 20 Pa. The storage modulus and loss modulus mentioned above can be measured by a commercially available rheometer.

[0056] As described above, the cosmetic composition is subjected to shear stress inside the pressurized polyurethane foam. receive Under shear stress, the composition of the present invention behaves like a liquid and flows easily inside the foam. Such flow characteristics can provide an advantage in uniform discharge of the cosmetic. For example, when used repeatedly several times, the composition of the present invention can flow and be rearranged quickly inside the impregnating material. When used, the composition inside the impregnating material is rearranged continuously, allowing for more uniform discharge during the period of use. In addition, since the flow characteristics of the composition can be improved by pressurization, the cosmetic composition can be easily impregnated by repeatedly pressurizing the foam during filling.

[0057] On the other hand, the composition of the present invention behaves like a solid when no shear stress is applied, which allows the composition to exist in a more stable state within the foam. In order to ensure stability when no stress is applied, it is preferable that the cosmetic composition has a relationship of G'>>G'', more specifically, a relationship of 3≦G' / G''≦10 at a shear stress of 1 Pa.

[0058] The cosmetic composition of the present invention comprises an oil phase component, an aqueous phase component, a thickener and a powder. These components and their contents determine the flow characteristics of the cosmetic composition.

[0059] The composition of the present invention may contain, in the entire cosmetic composition, 38 to 43% by weight of an oil phase component, 38 to 43% by weight of an aqueous phase component, 15 to 20% by weight of a pigment, and less than 1% by weight of a thickener.

[0060] In the present invention, the oil phase components can include an oil component, a film-forming agent, an ultraviolet blocking agent, and an emulsifier.

[0061] In the present invention, the emulsifier may include a main emulsifier and an auxiliary emulsifier. In the present invention, the emulsifier may be used in an amount of 8 to 12 parts by weight based on 100 parts by weight of the oil phase component.

[0062] In the present invention, the primary emulsifier comprises at least one material selected from the group consisting of lauryl PEG-10 tris(trimethylsiloxy)silylethyl dimethicone, lauryl PEG-9 polydimethylsiloxyethyl dimethicone and cetyl PEG / PPG-10 / 1 dimethicone.

[0063] In the present invention, the auxiliary emulsifier may be at least one of PEG-10 dimethicone and sorbitan isostearate.

[0064] In the present invention, the weight ratio of the primary emulsifier to the auxiliary emulsifier in the emulsifier is preferably 3: 1 to 4: 1. If the ratio of the primary emulsifier to the auxiliary emulsifier is less than 3: 1, the long-term formulation stability is reduced.

[0065] In the present invention, the weight ratio of the oil phase component to the aqueous phase component is preferably in the range of 0.9 to 1.1, more preferably 0.95 to 1.1. If the ratio of the aqueous phase component is less than this range, the emulsion stability drops sharply. EXAMPLES

[0066] In the following, preferred embodiments of the present invention are described.

[0067] A.Polyurethane foam Composite polyurethane foams were prepared by varying the ratio of polyester polyol to polyether polyol. For comparison, polyurethane foams containing 100% polyester polyol and polyurethane foams containing 100% polyether polyol were also prepared.

[0068] The composition of each polyurethane foam is shown in Table 1.

[0069] [Table 1]

[0070] To evaluate the hydrolysis characteristics of the manufactured polyurethane foam, polyester polyol foam and hybrid foam were immersed in 10% hydrochloric acid and nitric acid at room temperature for 7 days, and the collapse state of the foam was observed. To conduct the experiment under accelerated conditions, the acid catalysts hydrochloric acid and nitric acid were evaluated in aqueous solutions with a concentration of 10 wt% each. The experimental results are shown in Table 2.

[0071] [Table 2]

[0072] The ester oil, polar organic UV blocking agent, and volatile silicone oil contained in the raw materials of the cosmetic composition were each impregnated, and after maintaining at 80°C for 20 minutes, the size of each urethane foam was measured and compared with the volume of the foam before impregnation to confirm the degree of expansion of the volume of the foam, and the results are shown in Table 3. As the ester oil, cetyl ethylhexanoate, diisostearyl maleate, butylene glycol dicaprylate / dicaprate, dicaprylyl carbonate, and neopentyl glycol diheptanoate were used. As the polar organic UV blocking agent, ethylhexyl methoxycinnamate, hexylhexyl salicylate, and isoamyl-P-methoxycinnamate were used. As the volatile silicone oil, cyclohexasiloxane, cyclopentasiloxane, and cyclomethicone were used.

[0073] [Table 3]

[0074] B. Cosmetic Composition A W / O type cosmetic composition was prepared. An oil phase component containing an ultraviolet blocking agent, a film-forming agent, an emulsifier, and an oil component was mixed, heated to 80°C, and stirred to make the phase uniform. A powder was mixed therein and stirred again to uniformly disperse the powder component to prepare an oil phase component. A water phase component was mixed in a separate beaker, heated to 80°C, and stirred to completely dissolve the powder component to prepare an aqueous phase component. The prepared aqueous phase component was gradually added to the oil phase component prepared as above, and emulsified using a homomixer. The mixture was then cooled to 30°C to obtain the cosmetic compositions shown in Tables 5 to 7.

[0075] The cosmetic composition was designed to have a low critical shear stress at a water content of 30% by weight or less. The components and blending ratios (by weight) of the produced cosmetic composition are shown in Table 4.

[0076] [Table 4]

[0077] The specific blending ratios of Production Examples 1 to 3 are shown in Tables 5 to 7.

[0078] [Table 5]

[0079] [Table 6]

[0080] [Table 7]

[0081] The viscosity and flow properties of the cosmetic compositions of Preparation Examples 1 to 3 were measured. The viscosity was measured using a viscometer (DV-E Viscometer, Brookfield) after placing 100 g of each prepared composition in a plastic container. A spindle No. 4 was used for the viscosity measurement, and the spindle was immersed in each composition and rotated at 12 rpm for 1 minute, and the displayed value was used as the viscosity. The viscosity measurement results are shown in Table 6.

[0082] [Table 8]

[0083] The flow properties of the compositions of Preparation Examples 1 to 3 were measured using a cone-plate rheometer (MCR92, Anton Paar). The measurement frequency was 10 Hz. Figures 5 to 7 are graphs showing the measured storage modulus and loss modulus values, and Table 9 is a table summarizing the limit shear stress values ​​of Figures 5 to 7.

[0084] [Table 9]

[0085] C. Evaluation of repositioning properties of cosmetic compositions Impregnated foams were prepared by impregnating a PU3 foam having a thickness of about 10 mm and a diameter of about 5 cm with each of the compositions of Preparation Examples 1 to 3. The weight of the composition impregnated in each foam was 16 g. The impregnated PU3 foam was used as the lower PU3 foam, and the upper PU3 foam in a non-impregnated state was placed on top of it. Pressurization was performed so that the total thickness of the PU3 foam became 15 cm, and the pressurization was maintained for 10 seconds, and the relative weight loss of the lower PU3 foam was compared. As a result of the weight measurement, the order of weight loss was Preparation Example 1, Preparation Example 2, and Preparation Example 3. This is believed to be due to the fact that the lower the limit shear stress value of the impregnated composition, the more actively the composition flows into the upper PU3 foam, and the greater the weight loss of the composition in the lower PU3 foam.

[0086] From the above experiments, it was confirmed that a significant amount of weight loss occurred in the lower foam, and the composition was easily rearranged when pressurized. It was also found that a relatively large weight loss occurred in the case of a foam carrying a composition with a low critical shear stress value.

[0087] D. Evaluation of hardness before and after impregnation The hardness of PU1, PU3, and PU6 foams, each having a thickness of about 10 mm and a diameter of about 5 cm, was measured before and after impregnation. The impregnation composition was the composition of Preparation Example 2, and the impregnation amount was 16 g. For comparison, the hardness value of PU4 foam was also measured before and after impregnation. The hardness value was determined based on an ASKER hardness tester Type F. Figure 8 (a) and (b) are photographs taken during the process of measuring the hardness of PU3 foam before and after impregnation, respectively.

[0088] Table 10 shows the measurement results of the hardness and the hardness change rate of the PU2 foam used in the experiment.

[0089] [Table 10]

[0090] E. Sensory Evaluation After impregnating PU1, PU3 and PU6 polyurethane foams with the cosmetic composition of Preparation Example 1, a sensory evaluation was conducted on 20 women in their 20s and 30s who are skilled in evaluating cosmetics to confirm the difference in effectiveness according to the difference in hardness before and after the impregnation of the cosmetic. In this experiment, PU1, PU3 and PU6 foams were used as polyurethane foams to be evaluated for hardness, and the three types of polyurethane foams were all identical to the naked eye, and the sensory evaluation was conducted without any background information about the polyurethane foams to the subjects.

[0091] The sensory evaluation items were evaluated in three ways: discharge feeling, contact feeling, and usability, and were rated on a five-point scale of 5 points (very good), 4 points (good), 3 points (average), 2 points (bad), and 1 point (very bad), after which the average value was calculated. Each sensory evaluation item is explained below.

[0092] 1) Discharge feeling: Evaluate whether the amount of cosmetic composition discharged from the impregnating material onto an applicator (a general NBR puff) is appropriate. If the amount discharged in one discharge is too small, it will have to be taken multiple times, which will affect the durability of the impregnating material.

[0093] 2) Touch: Evaluate the sensory characteristics felt when the applicator touches the impregnating material.

[0094] 3) Usability: Evaluate the overall usability felt when applying the impregnated cosmetic composition with an applicator.

[0095] [Table 11]

[0096] As shown in Table 11, the sensory properties of the polyurethane foams of the Examples according to the present invention were evaluated as being superior to those of Comparative Examples 1 and 2. The item of note is the feeling of discharge, and it was confirmed that the feeling of discharge of the Examples, which had a low reduction rate before and after impregnation, was rated significantly higher than that of the Comparative Examples, which had a high reduction rate, and the excellent effect of the Examples was also confirmed in terms of the overall comfort of use.

[0097] Although the present invention has been described in detail through the embodiments of the present invention, the above description is merely illustrative of the present invention and is not intended to limit the present invention. It should be understood that the present invention is within the scope of the appended claims and the gist of the present invention, and that any person having ordinary skill in the art to which the present invention pertains may make various modifications within the scope of the present invention. [Industrial Applicability]

[0098] The present invention can be used in cosmetics. (Additional Note) Embodiments of the present disclosure also include the following. <1> A cosmetic product comprising a polyurethane foam impregnated with a cosmetic composition, The polyurethane of the polyurethane foam contains ether groups and ester groups in a molar ratio of 4:6 to 6:4, The cosmetic composition is characterized in that it has a water content of 35 wt% or less and a critical shear stress value, where storage modulus (G') = loss modulus (G''), of 100 Pa or less. <2> The cosmetic composition has a water content of 20 to 35 wt%. <1> The cosmetic product described in <3> The cosmetic composition has a water content of 20 to 30 wt%. <1> The cosmetic product described in <4> The cosmetic composition has a water content of 25 to 30 wt%. <1> The cosmetic product described in <5> The cosmetic composition is characterized in that the critical shear stress value is 20 Pa or less. <1> The cosmetic product described in <6> The cosmetic composition is characterized in that the critical shear stress value is 10 Pa or less. <1> The cosmetic product described in <7> The cosmetic composition is characterized in that the critical shear stress value is 5 Pa or less. <1> The cosmetic product described in <8> The cosmetic composition is characterized in that 3≦G′ / G″≦10 under a shear stress of 1 Pa. <1> The cosmetic product described in <9> The cosmetic composition comprises an oil phase component and an aqueous phase component, The weight ratio of the oil phase component to the aqueous phase component is in the range of 0.9 to 1.1. <1> The cosmetic product described in <10> The cosmetic composition comprises a primary emulsifier and an auxiliary emulsifier, and the primary emulsifier and the auxiliary emulsifier are in a weight ratio of 3:1 to 4:1. <1> The cosmetic product described in <11> The primary emulsifier comprises at least one substance selected from the group consisting of lauryl PEG-10 tris(trimethylsiloxy)silylethyl dimethicone, lauryl PEG-9 polydimethylsiloxyethyl dimethicone and cetyl PEG / PPG-10 / 1 dimethicone. <1> The cosmetic product described in <12> The auxiliary emulsifier comprises at least one of PEG-10 dimethicone and sorbitan isostearate. <1> The cosmetic product described in <13> The hardness of the polyurethane foam after impregnation is 20 to 35. <1> The cosmetic product described in <14> The hardness change rate of the polyurethane foam before and after the impregnation is 45% or less based on the hardness before the impregnation. <1> The cosmetic product described in

Claims

1. A cosmetic product comprising a polyurethane foam impregnated with a cosmetic composition, The polyurethane of the polyurethane foam contains ether groups and ester groups in a molar ratio of 4:6 to 6:4; The cosmetic composition has a water content of 20 to 30 wt %, and a critical shear stress value at the intersection of a storage modulus (G') curve and a loss modulus (G'') curve is 3 Pa to 15 Pa.

2. The cosmetic composition according to claim 1, wherein the cosmetic composition satisfies 3≦G′ / G″≦10 under a shear stress of 1 Pa.

3. The cosmetic composition comprises an oil phase component and an aqueous phase component, 2. The cosmetic product according to claim 1, wherein the weight ratio of the oil phase component to the water phase component is in the range of 0.9 to 1.

1.

4. 2. The cosmetic composition according to claim 1, comprising a primary emulsifier and an auxiliary emulsifier, the primary emulsifier and the auxiliary emulsifier being in a weight ratio of 3:1 to 4:1, the primary emulsifier comprising at least one substance selected from the group consisting of lauryl PEG-10 tris(trimethylsiloxy)silylethyl dimethicone, lauryl PEG-9 polydimethylsiloxyethyl dimethicone, and cetyl PEG / PPG-10 / 1 dimethicone, and the auxiliary emulsifier comprising at least one of PEG-10 dimethicone and sorbitan isostearate.

5. 2. The cosmetic product according to claim 1, wherein the hardness of the polyurethane foam after impregnation is 20 to 35.

6. 2. The cosmetic product according to claim 1, wherein the change in hardness before and after the impregnation with the polyurethane foam is 45% or less based on the hardness before the impregnation.

Citation Information

Patent Citations

  • Hybrid foam and cosmetic kit using same

    JP2019504681A